2005
DOI: 10.1002/jsfa.2125
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a free radical‐scavenging antioxidant from water spinach (Ipomoea aquatica Forsk)

Abstract: Ipomoea aquatica Forsk, a green leafy vegetable that is a rich source of vitamins and amino acids with many health benefits, has been explored for the isolation and identification of its bioactive compounds. Activity-guided repeated fractionation of a methanol extract on a silica gel column followed by an XAD column yielded a compound that exhibited antioxidant activity with an EC 50 value of 83 ± 1.02 µg ml −1 reaction mixture. It also showed very strong lipid peroxidation-inhibitory activity in a liposome mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
85
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 34 publications
11
85
0
2
Order By: Relevance
“…It was found that no investigation has been carried out for cytotoxic activities till now among our studied fourteen vegetables except Diaplazium esculentum and Ipomoea aquatica. In the present study, Ipomoea aquatica showed strong cytotoxic activity which is in accordance with the result obtained earlier [32] . On the other hand Diaplazium esculentum also displayed potent cytotoxic potential in our observations but in another report it was found to have no cytotoxic activity [77] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was found that no investigation has been carried out for cytotoxic activities till now among our studied fourteen vegetables except Diaplazium esculentum and Ipomoea aquatica. In the present study, Ipomoea aquatica showed strong cytotoxic activity which is in accordance with the result obtained earlier [32] . On the other hand Diaplazium esculentum also displayed potent cytotoxic potential in our observations but in another report it was found to have no cytotoxic activity [77] .…”
Section: Discussionsupporting
confidence: 93%
“…Glinus oppositifolius (L.) was found to contain immunomodulating peptic polymer, terpinoid saponine having antiprotozoal activity, and bioactives having antioxidant property [27][28][29] . Ipomoea aquatica Forsk was reported for hypoglycemic activity, cytotoxic activity [30][31][32] . Lagenaria siceraria was reported for its diuretic activity [33] , antihypertensive and cardioprotective effect [34] .…”
Section: P E E R R E V I E W Abstractmentioning
confidence: 99%
“…TPC for five fractions from longan pericarp was decreased in the following order LPEF > LPDF > LPBF > LPCE > LPR. Several reports (Duan et al, 2007;Li & Jiang, 2007;Prasad et al, 2005) have conclusively shown a close relationship between total phenolic content and antioxidant activity since phenolic compounds serving as hydrogen-donating agents. Sarikurkcu et al (2008) reported that dietary plants possessing substantial phenolic compounds may be health-benefit due to their antioxidant properties.…”
Section: Total Phenolic Contentsmentioning
confidence: 97%
“…Phenolic present in fruits and vegetables have received considerable attention because of their potential antioxidant activity. Phenolic compounds undergo a complex redox reaction with the phosphotungstic and phosphor-molybdic acids present in the Folin-Ciocalteu reagent (Prasad et al 2005). It was found that Ledang variety had a considerably lower total phenolic contents compared to Tambun variety (p <0.05).…”
Section: Total Phenolic Compoundsmentioning
confidence: 99%